Improved performance of polyaniline/reduced-graphene-oxide supercapacitor using atmospheric-pressure-plasma-jet surface treatment of carbon cloth. (10th January 2018) - Chien, Hung-Hua; Liao, Chen-Yu; Hao, Yu-Chuan; Hsu, Cheng-Che; Cheng, I-Chun; Yu, Ing-Song; Chen, Jian-Zhang
Abstract: This study evaluates carbon cloth treated using dc-pulse nitrogen atmospheric pressure plasma jet (APPJ) for a polyvinyl alcohol (PVA)/sulfuric acid (H2 SO4 ) gel-electrolyte supercapacitor with a polyaniline (PANI)/reduced graphene oxide (rGO) nanocomposite electrode materials. The water contact angle of the carbon cloth decreases from 144.71° to 0° after the scanning APPJ surface treatment. The improved wettability can facilitate the penetration of the electrolyte into the porous electrodes, thereby improving the capacitance. X-ray photoelectron spectroscopy (XPS) indicates the introduction of nitrogen doping into to the carbon fibers of carbon cloth through the nitrogen APPJ treatment. Without APPJ treatment of carbon cloth, the specific (areal) capacitance of the fabricated supercapacitor is 315.0 F g −1 (55.67 mF/cm 2 ); it increases to 580.2 F g −1 (106.89 mF/cm 2 ) with APPJ surface treatment of carbon cloth before screen-printing the PANI/rGO nanocomposite. Electrochemical impedance spectroscopy (EIS) indicates a decreasing charge-transfer impedance at the electrode/electrolyte interface for supercapacitors with APPJ treatment of carbon cloth. This also improves the supercapacitive performance. After 1000-cycle cyclic voltammetry stability test, the capacitance retention rate is ∼85%. Our experimental results suggest that nitrogen dc-pulse APPJ in scanning mode is an efficient tool for enhancing the supercapacitance performance of a PANI/rGO supercapacitor. Graphical abstract: Highlights: APPJ is used for surface treatment of carbon cloth for PANI/rGO supercapacitor. With APPJ treatment, specific capacitance improves from 315.0 to 580.2 F g −1 . Charge-transfer impedance decreases with APPJ treatment of carbon cloth. APPJ treatment introduces nitrogen doping and improves wettability.